2017
DOI: 10.3390/ijms18081813
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Better Understanding of GABAergic Remodeling in Alzheimer’s Disease

Abstract: γ-aminobutyric acid (GABA) is the primary inhibitory neurotransmitter in the vertebrate brain. In the past, there has been a major research drive focused on the dysfunction of the glutamatergic and cholinergic neurotransmitter systems in Alzheimer’s disease (AD). However, there is now growing evidence in support of a GABAergic contribution to the pathogenesis of this neurodegenerative disease. Previous studies paint a complex, convoluted and often inconsistent picture of AD-associated GABAergic remodeling. Giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
90
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 167 publications
(109 citation statements)
references
References 343 publications
2
90
0
2
Order By: Relevance
“…Analysis of the indexes for temporal-scale-dependent complexity has shown that this reduction of complexity especially concentrates in fast wave components (34,36). Studies of neurotransmitter changes in AD have reported that dysfunction of the gamma-aminobutyric acid (GABA) signaling system, which is caused by the deposition of amyloid-b and tau proteins, leads to reduced oscillatory gamma band activity (68)(69)(70). The impairment of gamma oscillatory activity might lead the complexity at faster temporal scales more than slower temporal scales (34,36).…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of the indexes for temporal-scale-dependent complexity has shown that this reduction of complexity especially concentrates in fast wave components (34,36). Studies of neurotransmitter changes in AD have reported that dysfunction of the gamma-aminobutyric acid (GABA) signaling system, which is caused by the deposition of amyloid-b and tau proteins, leads to reduced oscillatory gamma band activity (68)(69)(70). The impairment of gamma oscillatory activity might lead the complexity at faster temporal scales more than slower temporal scales (34,36).…”
Section: Resultsmentioning
confidence: 99%
“…It is now well-known that GABA, in addition to glutamate, maintains the excitatory/inhibitory balance, and plays a compensatory role in memory processing (Lanctôt, Herrmaan, Mazzotta, Khan, & Ingber, 2004;Obata, 2013). The importance of GABAergic pathways in remodeling of the AD brain has also been suggested and highlights its role in compensating for the learning and memory impairments in the early stages of AD (Govindpani et al, 2017). Therefore, the GABAergic system is an essential target for the design of novel disease-modifying drugs, although its role in the disease pathogenesis and the cellular changes underlying AD has not been extensively studied (Calvo-Flores Guzmán et al, 2018).…”
Section: Gammapyrone Effects On the Gabaergic System In A Male Ratmentioning
confidence: 99%
“…It is important to point out that, other potential factors might also contribute to the altered extrasynaptic GABA levels, from changes in GABA uptake and clearance processes. Furthermore, remodeling of GABA A R subunit expression, along with alteration of the expression of GABA transporters (GATs) in the AD brain, may buffer changes in synaptic GABA levels, and ultimately, affect the total levels of extrasynaptic GABA [16][17][18][19][20]. test (* p = 0.0382, ** p = 0.0025; NC n = 4, ACSF-injected n = 4, and Aβ 1-42 -injected n = 5).…”
Section: Resultsmentioning
confidence: 99%
“…However, other neuropathological processes are likely to contribute to the dysfunctional E/I network balance in the hippocampus that leads to cognitive deterioration. Although cognitive decline in AD has been largely related to Aβ oligomers and the glutamatergic system through multiple interactions [31,32], there is growing evidence to suggest that cognitive decline in the AD brain is influenced and also partly precipitated by altered GABAergic function [19], and this has been linked to cognitive decline [33]. In the extrasynaptic space, Aβ 1-42 mediates increase in ambient GABA levels which chronically activates tonic inhibitory currents in the hippocampus, that are involved in the maintenance of the excitatory network and synchronization, and in turn might contribute to the cognitive deficits -but the exact mechanism requires further elucidation.…”
Section: Resultsmentioning
confidence: 99%